Audio-visual materials and services at the University of the Philippines - Cay, Marinella B.; Hidalgo, Namnama P.; Castillo, Jovito B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
Educational technology has seen an increasing role in the teaching-learning process in the past decade. The use of audio-visual materials provides a concrete basis for conceptual thinking and hence reduces meaningless word responses of students; makes learning more permanent; offers a reality of experience which stimulates self-activity on the part of the pupils; develops a continuity of thought; contributes to the growth of meaning, and hence to vocabulary development; provides experiences not easily obtained through other materials; and contributes to the efficiency, depth, and variety.
The descriptive normative approach was used in this study. For data gathering, a questionnaire of five parts (Selection and Acquisition, Cataloging and Classification, Circulation, Personnel, and Administration and Budgeting) was administered to the officers-in-charge of the audio-visual services in each unit/college. Interviews with these officers-in-charge were also conducted. The physical aspects of the A-V laboratories were observed. Finally, research into the different catalogues, bulletins, and syllabi of the UP System and the specific colleges in the survey and into various libraries/media centers was undertaken. The respondent units/colleges were chosen using the following criteria: 1) their having audio-visual collections since their organization; 2) their being logically dependent on A-V materials as called for in their curriculum; and 3) upon the suggestion by the writer's adviser and reader.
The findings are: 1) Quantitatively and qualitatively, the A-V holdings in the thirteen units/colleges are still below accepted standards for an educational institution of its size and importance. 2) There is no systematuc procedure followed by the A-V units regarding the selection and acquisition, cataloguing and classification, circulation, and administration of A-V materials/equipment and services. 3) The A-V units are understaffed and majority of the personnel have no knowledge of acquisition, cataloguing, classification and circulation procedures. 4) The most pressing problems include lack of funding, lack of knowledge of scientific organizations and implementation of A-V services, and lack of personnel, both in number and professional expertise. 5) A UP Audio-Visual Center is considered feasible. 6) The most used media are the 2" x 2" slides, films, filmstrips, tapes and disc recordings while the most common equipment holdings are the slide projector (2" x 2"), 16mm movie projector, the cassette recorder and the record player. 7) The A-V centers showed a need for separate administrative policies for A-V services. 8) There is a need for a periodic evaluation of A-V services. 9) There is a need for dissemination of information among faculty members regarding the availability of A-V materials and equipment in the units/colleges assigned to these functions. 10) There is a need to update and replenish existing holdings.
In order to develop existing educational technology materials and facilities towards fuller utilization of A-V services in the instructional programs of the UP, it is recommended that: 1) The University should be rpovided with a well-organized audio-visual program adequately equipped with materials and machinery. 2) Financial support for A-V resources and services should be an integral part of the economic structure of the University. 3) A program of inter-A-V center lending of resources and a time-sharing of equipment should be set up for more extensive coverage of needs, for decreasing time wasted, and for maximum use of available materials and equipment. 4) Cooperative ventures such as the making of a union catalogue of A-V resources and equipment and cooperative acquisitions of materials and equipment should be done preferably by a central A-V unit. 5) There should be a continuing development and refinement, both qualitatively and quantitatively, of audio-visual collections and services. 6) Needed guides and reviewing media concerned with audio-visual equipment, materials, and related efforts should be circulated to help units in their acquisition and selection responsibilities. 7) Training activities, such as institutes, workshops, conferences, and seminars should be fostered and encouraged. 8) Improvement of communication and a regular means of coordinating audio-visual projects should be launched and maintained by the existing units until a central A-V system is set up to take care of such a function. (9) The UP System should, in the absence of a central A-V system, encourage by budgetary support and recognition, the building up of the Audio-Visual Center of the college of Education into a model display and demonstration A-V center for the Philippine educational system. (10) Librarians in the field should be encouraged to take educational courses and individuals engaged in audio-visual services should be encouraged to take basic library science courses in order to produce the much desired media specialists.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Audiovisual library service--Philippines--Quezon City; Audiovisual materials--Philippines--Quezon City; University of the Philippines Diliman